The Sequential Search Model: A Framework for Empirical Research - Raluca Ursu; Stephan Seiler; Elisabeth Honka (Center for Economic Studies and ifo Institute (CESifo), 2023)
We provide a detailed overview of the empirical implementation of the sequential search model proposed by Weitzman (1979). We discuss the assumptions underlying the model, the identifica-tion of search cost and preference parameters, the necessary normalizations of utility parameters, counterfactuals that require a search model framework, and different estimation approaches. The goal of this paper is to consolidate knowledge and provide a unified treatment of various aspects of sequential search models that are relevant for empirical work.
Keywords: D43; D83; L13; 330; sequential search model